1996
DOI: 10.1289/ehp.961041084
|View full text |Cite
|
Sign up to set email alerts
|

Identification of environmental chemicals with estrogenic activity using a combination of in vitro assays.

Abstract: Environmental chemicals that function as estrogens have been suggested to be associated with an increase in disease and dysfunctions in animals and humans. To characterize chemicals that may act as estrogens in humans, we have compared three in vitro assays which measure aspects of human estrogen receptor (hER)-mediated estrogenicity. Chemicals were first tested for estrogen-associated transcriptional activity in the yeast estrogen screen (YES). This was created by expressing hER and two estrogen response elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(94 citation statements)
references
References 26 publications
4
88
1
1
Order By: Relevance
“…To examine the effects of the ER on AP-1-mediated gene expression by environmental compounds, we generated from Figure 3B). This result and the fact that o,p´-DDD has virtually no ER binding activity (19,21), indicates a non-ER-mediated AP-1 signaling mechanism. p,p´-DDA, a metabolite found in humans, had no effect on AP-1 activity.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…To examine the effects of the ER on AP-1-mediated gene expression by environmental compounds, we generated from Figure 3B). This result and the fact that o,p´-DDD has virtually no ER binding activity (19,21), indicates a non-ER-mediated AP-1 signaling mechanism. p,p´-DDA, a metabolite found in humans, had no effect on AP-1 activity.…”
Section: Resultsmentioning
confidence: 92%
“…However, this chemical is still used in many developing countries today and exists at high concentrations along with its metabolites and contaminants throughout the world, including the United States, because of long half-lives in soil, water, and the adipose tissue of animals (24,28,30,(75)(76)(77). Although DDT and some of its metabolites bind ERs (16,19,21), induce egg-shell thinning in raptors (78,79), and induce estrogen-like effects in exposed animals and humans (1,22,25), the mechanisms of action of this class of synthetic compounds is still not completely understood. Here we have shown that DDT can directly affect the activity of AP-1, an important cell regulatory factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insecticide chlordane and the herbicide alachlor did not stimulate the proliferation of breast cancer cells (3). Recently, alachlor was reported to have weak estrogenic activity with the human estrogen receptor (hER) in breast cancer cells and yeast using reporter-gene assays (4).…”
mentioning
confidence: 99%
“…[1][2][3][4] Endocrine disrupters include such degradation products of alkylphenol polyethoxylates (APPEOs) as nonylphenol polyethoxylates (NPPEOs) and octylphenol polyethoxylates (OPPEOs) that are commercially important surfactants. APPEOs are composed of a phenol nucleus that is o, m, and p-substituted with a hydrophobic and branched alkyl moiety, and with a hydrophilic polyethylene glycol chain linked to the phenolic oxygen.…”
Section: Isolation Of Bacterial Strains That Produce the Endocrine DImentioning
confidence: 99%